PENERAPAN ARSITEKTUR TRADISIONAL SUKU SASAK DALAM PERANCANGAN NOVOTEL LOMBOK RESORT AND VILLAS - Davis Tjandra; Indri Astrina Fitria Indrarani (Riset Arsitektur (RISA), 2024)
Abstract - Indonesia is rich having so much diversity in traditional architecture. Not only art and culture, each region have it’s own unique architecture that can be seen in the traditional houses across Sabang to Merauke. In an era with a very rapid development, global influence can threaten Indonesia’s traditional architecture. Globalization tends to make people prefer architecture with the western style. Traditional architecture is very vulnerable to be influenced and modified to suit the new needs and demands. This can threaten the existence of Indonesia’s traditional architecture. It becomes very important to preserve traditional architecture so that its existence is not further eroded. The purpose of this study is to find out what local aspects and elements of the Sasak Tribe are adopted to the design of Novotel Lombok Resort and Villas. This research will use descriptive qualitative research methods, namely methods that use qualitative data and described descriptively. This method is used to analyze phenomena, problems or social conditions. The research process will use the theory of house architecture, form and culture from Amos Rapoport as the main reference, data obtained from survey results on the object of study, observations and interviews with related parties including building managers to complete the analysis. Findings This research is expected to be able to contribute academically and non-academically to society. Novotel Lombok Resort and Villas is designed based on the traditional architectural concept of the Sasak Tribe by applying architectural aspects and elements that can also be found in settlements and buildings of the Sasak Tribe. The adoption is dominant in the use of materials, construction and building technology used, especially in the upper or roof enclosure. It was also found that the adoption of other architectures, namely the architecture of the Musalaki House, Sumba Tribe, West Nusa Tenggara as an effort to introduce Indonesian architecture and culture more broadly. Some aspects and elements of traditional architecture in the resort area are not maintained and are damaged. In fact, due to the difficulty of maintenance, one of the roofs of the building replaced the materials and construction used in the renovations carried out in 2010. This can certainly be an example case study for the future. Keywords: Traditional Architecture, Sasak Tribe, Adoption, Novotel Lombok